1983
DOI: 10.1039/an9830801396
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise complexometric determination of calcium and magnesium in the presence of a high manganese and iron content using potassium hexacyanoferrate(II) as a masking agent

Abstract: A critical study has been made on the masking of manganese and iron by their precipitation as Fe,[Fe(CN),] and Mn,[Fe(CN),J with K4[Fe(CN),] in the presence of ascorbic acid and potassium chloride for the complexometric titration of calcium plus magnesium with EDTA a t p H 10. The optimum acid concentration and temperature for the selective and quantitative precipitation of Mn (I I) and Fe( I I) liexacyanoferrates (I I), which are granular and nonadsorbant metallochromic indicators, are found to be 1-2.5 N hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, its application in analytical chemistry is less widely used. We found a few interesting examples in the literature: Dasgupta et al used air bubbling to overcome the interference of high manganese content based on the oxidation of Mn(II)-TEA to Mn(III)-TEA during the titration of calcium at pH 12; 1 Idowu et al used ambient air to generate ozone in a gas-phase chemiluminescence-based analyser for waterborne arsenic; 2 Pereira et al reported methods for the determination of Mn and Ni in lake and marine sediment slurries by GFAAS, in which slurries were kept homogeneous by air bubbling with an aquarium pump; 3 Camou et al described a portable sensor for measuring benzene in water based on bubbling extraction and UV spectroscopy detection. 4 Air has also been widely used in flow-based systems for segmentation or as a carrier.…”
Section: Introductionmentioning
confidence: 99%
“…However, its application in analytical chemistry is less widely used. We found a few interesting examples in the literature: Dasgupta et al used air bubbling to overcome the interference of high manganese content based on the oxidation of Mn(II)-TEA to Mn(III)-TEA during the titration of calcium at pH 12; 1 Idowu et al used ambient air to generate ozone in a gas-phase chemiluminescence-based analyser for waterborne arsenic; 2 Pereira et al reported methods for the determination of Mn and Ni in lake and marine sediment slurries by GFAAS, in which slurries were kept homogeneous by air bubbling with an aquarium pump; 3 Camou et al described a portable sensor for measuring benzene in water based on bubbling extraction and UV spectroscopy detection. 4 Air has also been widely used in flow-based systems for segmentation or as a carrier.…”
Section: Introductionmentioning
confidence: 99%